PENGARUH LABEL HALAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM CIREBON - Dian Wulandari, Oryz Agnu; Nurhimawan, Evan; Rofik, Muhamad; Wulandari, Kasih; Kurniawan, Putri Nur Shafa (Jurnal EBI, 2023)
Micro, Small and Medium Enterprises (MSMEs) are forms of business activities operated by individuals, groups, or small business entities with the aim of making a profit. MSMEs in Cirebon are one of the growing business sectors in recent years. The key to the success of MSME businesses is their ability to meet growing consumer demands. The important thing for MSMEs today is products with halal certification and products with guaranteed quality. This study aims to (1) To determine the influence of halal labels on the purchase decision of MSME products in Cirebon, (2) To determine the influence of product quality on the purchase decision of MSME products in Cirebon, (3) To determine the effect of halal labels and product quality simultaneously on the purchase decision of MSME products in Cirebon, and (4) To find out what factors influence consumers in considering halal labels and product quality in purchasing decisions for MSME products in Cirebon. In the design of this study using a quantitative approach with descriptive and associative research methods to test hypotheses about the influence of halal labels and product quality on consumer purchasing decisions on MSME products in Cirebon. The results of the analysis show that halal labels and product quality have a partial or joint effect on consumer purchasing decisions of MSME products in Cirebon.Key words: influence of halal label, influence of product quality, purchasing decision, sme, cirebon